Reduced in vivo binding to the serotonin transporter in the cerebral cortex of MDMA ('ecstasy') users. - Semple, D; Ebmeier, K; Glabus, M; O'Carroll, R; Johnstone, E (1999)
BACKGROUND: The use of MDMA ('ecstasy') is common among young people in Western countries. Animal models of MDMA toxicity suggest a loss of serotonergic neurons, and potentially implicate in the development of significant psychiatric morbidity in humans. AIMS: To test whether long-term use of MDMA can produce abnormalities in cerebral serotonin, but not dopamine, transporter binding measured by single photon emission computed tomography (SPECT). METHOD: Ten male regular ecstasy users and 10 well-matched controls recruited from the same community sources participated in SPECT with the serotonin transporter (SERT) ligand [123I] beta-CIT. Dopamine transporter binding was determined from scans acquired 23 hours after injection of the tracer. RESULTS: Ecstasy users showed a cortical reduction of SERT binding, particularly prominent in primary sensory-motor cortex, with normal dopamine transporter binding in lenticular nuclei. CONCLUSIONS: This cross-sectional association study provides suggestive evidence for specific, at least temporary, serotonergic neurotoxicity of MDMA in humans.